The uses of fear: Spatial politics in the Australian white-vanishing trope - Tilley EN (American association of Australian Literary Studies, 2009)
This article discusses the fear of the unknown exhibited in the trope of Australian literature involving disappearing whites. The various forms of the trope are described, which include tales of lost children, missing explorers, or disappearing drovers. The exhibition of the white European fear of the unknown area beyond the European sphere of influence within such stories is noted.
Keywords: 19 Studies in Creative Arts and Writing; 20 Language, Communication and Culture